TINGKAT KEPUASAN PELANGGAN SISWA KELAS 9 SMP LAB HAMZANWADI PANCOR TERHADAP PELAYANAN ADMINISTRASI SEKOLAH TAHUN AJARAN 2018-2019 - m.rudi gunawan parozak; Fadma Rosita (JUPE : Jurnal Pendidikan Mandala, 2019)
This study aims to determine the response of students to the academic administration services to the students of class 9 in junior LAB Hamzanwadi Pancor , and aspects of what has the most excellent response and aspects that need to be improved from the manager. The method of research this is a study case with qualitative research in Intitiu Global Nusantara Education (IPNG) . The data source used was 9th grade students , Administration, and document sources in the form of Academic Guidelines for Junior High School LAB 2019 . Data obtained from interviews with source triangulation techniques and triangulation methods. Analysis of the data is done with meaning through the following phases: the data collection , the data reduction, data display , and data verification. Research findings on aspects of academic administration services in SMP LAB Hamzanwadi Pancor in general, students stated quite well. In the aspect of learning by teachers in the classroom are generally well categorized. Expectations on administrative and academic services indicate that there are still many aspects that need to be improved and need to get clear supervision and continuous controlled maintenance. The aspects that have the best response are the aspects of personality, communication, mastery of learning material , learning plans and learning strategies. While aspects that still need to be improved are the problem of wify ( hotspot ) and the availability of learning facilities in the classroom and in the Library.